Base of tongue/tonsillar and laryngeal cancer in Denmark 1994–2018: Temporal trends in incidence according to education and age. (May 2022) - de la Cour, Cecilie Dovey; Munk, Christian; Aalborg, Gitte Lerche; Kjaer, Susanne Krüger
Highlights: Base-of-tongue/tonsillar and laryngeal cancer incidence trends may differ by education and age. Laryngeal cancer incidence is increasing only in individuals with short education. Base-of-tongue/tonsillar cancer incidence is increasing in virtually all age-groups. Abstract: Objectives: Base-of-tongue (BOT)/tonsillar cancer incidence is rising, primarily due to human papillomavirus; meanwhile, rates of the mainly smoking-associated laryngeal cancer is declining. Little is known about whether these trends are seen in all socioeconomic levels and age-groups. We describe incidence trends of BOT/tonsillar and laryngeal cancer in Denmark 1994–2018 by educational level and age. Methods: BOT/tonsillar and laryngeal cancer cases diagnosed 1994–2018 were identified from the Danish Cancer Registry. We obtained individual-level educational information from nationwide registries. We estimated age-standardized incidence rates of BOT/tonsillar and laryngeal cancer according to sex, education and age. Temporal incidence trends were evaluated by the average annual percentage change (AAPC) with corresponding 95% confidence intervals (CIs) using linear and Poisson regression models for age-standardized incidence rates. Results: We identified 4245 individuals with BOT/tonsillar cancer and 6123 with laryngeal cancer. BOT/tonsillar cancer incidence increased among men with short (AAPC:3.4, 95% CI 2.1;4.6) and long (AAPC:5.1, 95% CI 3.2;7.1) education, and all age-groups, while decreased from 2012 among men with medium education (AAPC:-4.3, 95 %CI −7.6;-1.0). Laryngeal cancer incidence decreased from 2007 in men with medium (AAPC:-4.7, 95% CI −6.7;-2.7) and long (AAPC:-2.4, 95% CI −3.4;-1.4) education, and all age-groups, whereas increased in men with short education (AAPC:1.0, 95% CI 0.2;1.8). Similar trends were seen among women. Conclusions: Over the last 25 years, BOT/tonsillar cancer incidence in Denmark has generally increased in all age-groups and educational levels. In contrast, social inequality was seen in laryngeal cancer trends as incidence decreased in individuals with medium and long education, while incidence increased in individuals with short education.